Analysis of the Effects of Economic Growth, Population, Education, and Wage on Labor Absorption in East Java - Amalia, Adzania Putri; Syafitri, Wildan (Journal of Development Economic and Social Studies, 2025)
Human resources are pivotal in driving economic development. However, Indonesia continues to face significant challenges in its labor sector. East Java ranks as the province with the second-highest unemployment rate in the country, highlighting the persistent issue of insufficient labor absorption. Various factors contribute to this phenomenon. This research investigates the impact of economic growth, population dynamics, education levels, and wage rates on labor absorption in East Java 2014 to 2023. Utilizing a quantitative approach, the study relies on secondary data provided by the Badan Pusat Statistik (BPS). The analysis is conducted using panel data regression through a series of steps, including model selection, classical assumption testing, and significance evaluation. The results demonstrate that economic growth, population size, education, and wages significantly and positively influence labor absorption in East Java during the observed period.